J.S. Bach's Material and Spiritual Treasures : a Theological Perspective - Heber, Noelle M., 1982- (Boydell & Brewer, 2021)
An innovative study of the ways in which theological themes related to earthly and heavenly 'treasures' and Bach's own apparent attentiveness to the spiritual values related to money intertwined in his sacred music.